Komunikasi Publik Humas Terminal Tirtonadi Surakarta dalam Kegiatan Edutrip - Nur’Aini Purwaningsih; Esfandani Peni Indreswari; Rahmat Wisudawanto (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Public communication plays a crucial role in delivering targeted transportation information and building a positive image of government institutions in the eyes of the public. One concrete implementation of effective public communication is the Edutrip program, an educational initiative from Surakarta's Tirtonadi Terminal designed to improve public transportation literacy, particularly among students and teachers. This program is not merely an educational visit, but also a strategic tool for Tirtonadi Terminal Public Relations to introduce the terminal's function as a modern and integrated transportation service center. This study aims to analyze the public communication strategies implemented by Tirtonadi Terminal Public Relations in implementing Edutrip, with a primary focus on their interactions with students and teachers as participants. Using a qualitative descriptive approach, the results show that Tirtonadi Terminal Public Relations predominantly applies the Public Information model from Grunig and Hunt (1984), namely by conveying one-way information that is educational and factual. However, in practice, elements of the Two-Way Symmetrical model were also found, particularly through question and answer sessions, discussions, and gathering feedback from participants which were then used as evaluation material for future program improvements. In contrast, the Press Agentry and Two-Way Asymmetrical models did not appear dominant, given that the approach used did not focus on excessive promotion or information manipulation, but rather on objective and dialogical education. This adaptive and responsive communication strategy not only increased participants' understanding of public transportation but also helped shape the positive image of Tirtonadi Terminal as a transparent, professional, and educational public institution. These findings emphasize the importance of selecting an appropriate and contextual communication model in building constructive relationships between public institutions and the community.